Principles of RF and microwave design - Morgan, Matthew A. (Artech House microwave library., 2020)
Packed with references and examples, this comprehensive resource provides a thorough introduction to the principles of electronic circuits operating in the radio, microwave, and millimeter-wave frequency ranges. --